Remotely inserted venous occlusion catheters for the control of venous haemorrhage. - Smith, S. R. (Royal College of Surgeons of England, 1988)
This paper describes the use of venous occlusion catheters inserted via the long saphenous vein or its tribularies for control of major retroperitoneal venous haemorrhage. The technique has been applied successfully in 10 cases of trauma and aortocaval fistula. Exposure and insertion are simple and quick and a measure of control is obtained before exposure of the injury which can then be completely repaired before deflation of the balloon and withdrawal of the catheter.